Iowa Birdline update, September 27, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for September 27, 1993. Highlights include sightings of a Gyrfalcon, Western Grebe and Yellow Rail. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed